Wound Healing Activity of Phyllanthus niruri in Albino Wistar Rats - Venkateshwarlu, Goli; S.K., Veliyath; Vijayabhaskar, Kanakam; Harishbabu, K.; Malothu, Ravi; Sahoo, Subhas (Asian Journal of Chemistry, 2012)
The entire wound healing process is a complex series of events that begins at the moment of injury and can continue for months to years. The objective of present study is to investigate wound healing activity of the chloroform leaf extract of Phyllanthus niruri in albino rats using excision and incision wound models. 200 mg/kg/day of leaf extract of Phyllanthus niruri was evaluated for its wound healing activity and compared with neosporin (standard). The present investigation may be concluded that the plant Phyllanthus niruri is endowed with significantly as followed the 0, 4th, 8th, 12th, 16th, days i.e. 232.21 ± 5.8 (0 %), 197.8 ± 4.5 (14.85 %), 80.7 ± 4.8 (65.5 %), 15.03 ± 2.9 (91.9 %), 2.9 ± 1.04 (98.8 %) wound healing activity due to the presence active constituents, there by justifying its use in the indigenous system of medicine.